Characteristics and kinetics of coal char steam gasification under microwave heating. (15th November 2019) - Liu, Quanrun; He, He; Li, Haipeng; Jia, Jianbo; Huang, Guangxu; Xing, Baolin; Zhang, Chuanxiang; Cao, Yijun
Highlights: Coal char was gasified by steam using microwave heating (MH) and conventional heating (CH). Higher carbon conversion rate and better quality of gas product can be obtained in gasification using MH. The kinetics of char steam gasification were described using SCM models. The kinetics parameters of char steam gasification under MH and CH were obtained and compared. Abstract: The behavior and kinetics of coal char steam gasification under microwave heating are investigated. The influence of the coal char particle size, water injection rate, and reaction temperature on the carbon conversion rate and gas product evolution during microwave heating gasification are considered and compared to the results from coal char steam gasification using conventional heating under the same conditions. The results show that microwave heating can accelerate the reaction rate of coal char steam gasification and improve the quality of the gas product. It was found that at temperatures varying from 600 to 900 °C, the coal char steam gasification reaction was well described using the shrinking core model (SCM). Activation energies of 82.8 kJ/mol and 114.3 kJ/mol were obtained for microwave heating and conventional electric heating, respectively.